THE DEPARTMENT STORE CONTROLLER'S PART IN BUSINESS POLICY. - Paynter, John W. (The Accounting Review, 1947)
Abstract The business policies of a department store, like any other sound business enterprise, are finally decided by top management, generally the corporate officers or the Board of Directors. These policies, once laid down, must be administered by the next immediate echelon of operating personnel consisting of the merchandise manager, the general superintendent or store manager, the publicity director and the controller. One of the major problems in retailing today, from the controller's viewpoint, is that of adequate merchandise control. The emphasis has been the need for carrying such techniques through to the point of benefit to every branch of the business. There has been an attempt also to talk of speed—shorter time lapses between the occurrence of an event and the recording and reporting of that event—and finally there has been an attempt to tell that accounting, at least in an organization is a process of seeking the best manufacturing techniques to enable to produce a fast, dependable and low-cost tool which has a very positive effect on shaping business policies because it is not a dusty, historical record over which to hold post-mortems, but instead it is a live, current force from which such policies can be created.